Dermatology Match Preference Signaling Tokens: Impact and Implications. Issue 12 (December 2022) - Dirr, McKenzie A.; Brownstone, Nicholas; Zakria, Danny; Rigel, Darrell
Abstract : BACKGROUND: The dermatology residency application process implemented a new system of preference signaling tokens (PSTs) in the 2021-2022 cycle to allow applicants to express a higher level of interest in specific programs. Limited data are available on the utilization and impact of these tokens. OBJECTIVE: To determine the impact of PSTs on the application process and where in the process PSTs had the greatest influence. MATERIALS AND METHODS: A 14-question survey was sent to 62 ACGME-accredited dermatology residency programs. Primary outcomes were PST impact on 2021-2022 applications. Variables were evaluated using open-ended questions, yes/no responses, and importance ratings from 0 to 100. RESULTS: An average of 7.1% of applicants were offered interviews, but 21.1% of applicants that submitted PSTs were interviewed versus 3.7% of nonsubmitters. 22.5% of ranked applicants and 19% of matched applicants submitted a PST to that program. Limitations: Not all programs responded, and PST submission restrictions could not be assessed. CONCLUSION: The greatest PST impact was on the interview decision but had minimal subsequent impact. Given PSTs cannot be submitted to home programs or in-person away rotations, the actual impact was probably greater than found. Programs will continue to implement PSTs in future cycles.